OP0062 Safety and Efficacy of Etanercept in Children with the JIA Categories Extended Oligoarthritis, Enthesitis Related Arthritis and Psoriasis Arthritis. (23rd January 2014) - Windschall, D.; Horneff, G.
Abstract : Background: The approval of the recombinant TNF receptor fusion protein etanercept for the treatment of the JIA categories resistant extended Oligoarthritis (ExOA), enthesitis related arthritis(ERA) and psoriasis arthritis (PSA) was actually added to the German approval for the treatment of resistant polyarticular juvenile arthritis. Objectives: To evaluate the efficacy and safety in the additional JIA category patients treated with Etanercept. Methods: Baseline demographics, clinical characteristics and disease activity parameters have been documented. Efficacy was determined using the PedACR 30/50/70 response criteria and the JADAS 10 activity score. Safety assessments were based on adverse events reports from the primary responsible physician. Results: Until December 31st, 2012 238 patients with ERA, 315 patients with ExOA and 127 patients with PSA were admitted to the registry. Especially the percentage of patients with ERA was increasing over the last decade. Patients in all additional approved indications and categories showed significant improvement in most parameters of disease activity between baseline and last observation. All mentioned categories started with a mean baseline JADAS 10 activity score over 15 ( RF positive 19, 3; RF negative 18, 3; ExtOA 17, 5; ERA 16, 0 and PSA 15, 2) and developed significant response to the treatment after 3 months (RF positive 8, 2 ; RF negative 7, 25; ExtOA 5, 4; ERA 4, 3; PsA 4, 8 ) and after 24 months (RF positive 4, 7; RF negative 5, 1; ExtOA 2, 6; ERA 4, 0 and PSA 4, 8). Serious and nonserious adverse events rates seem similar in all JIA categories, especially with respect to infections. However, rate of uveitis flares were higher in PSA (3.3/100Patyears[95%CI 1.6-6.7], ExtOA (2.8[1.8-4.3]) and ERA (2.7[1.5-4.9]) than in RF negative (1.3[0.8-2.2]) or RF positive (0.3[0.05-0.7]). Chronic inflammatory bowel disease occurred more frequently in ExtOA (0.73[95%CI 0.3-1.7], ERA (0.49[0.1-1.8]) and PSA (0.47[0.09-0.89]) than in RF negative (0.26[0.1-0.55]) or RF positive (0[0-0.51]). Conclusions: These data emphasises that administration of etanercept in patients with the JIA categories resistant extended oligoarthritis, enthesitis related arthritis and psoriasis arthritis is safe and very efficacious in children. Attention should be payed to the occurrence of extraarticular autoimmunopathies like uveitis flares and chronic inflammatory bowel disease. Disclosure of Interest: D. Windschall Grant/research support from: Pfizer, G. Horneff Grant/research support from: Pfizer, Abbott, Roche